Planning and management of the failed Urban Train Project for the City of Santa Fe (Argentina, 2007-2019) (Revista Iberoamericana de Estudios Municipales, 2025)
The objective of this paper is to address the planning and management of an urban rail project promoted by the city council of Santa Fe (Argentina) between 2007 and 2019. It had to use national infrastructure, which led into a complex permit application. Furthermore, there was limited support from the provincial government and mechanical failures in the vehicles purchased by the council, all factors that led to the failure of the public policy. The work was made using a qualitative methodological approach and it based on several research techniques. The article appeal to the concept of state capacity and its analytical dimensions to interpret the findings as consequences of poor inter-institutional coordination.
Keywords: planning; management; public transport